Iterative method of derivation by unified formula (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2019)
Objective: This research was conducted with the aim of proposing a derivation method that unifies all known traditional methods. Method: Quantitative research was carried out, collecting information from surveys conducted with students and teachers. Results: Students applied the iterative method (a single formula) in the derivation of basic functions, obtaining the same result as when using the traditional method (several formulas), and in less time. Conclusions: This new method is useful in calculus courses in both formal education and higher education.